2015
DOI: 10.1002/2014jg002791
|View full text |Cite
|
Sign up to set email alerts
|

Climate response of the soil nitrogen cycle in three forest types of a headwater Mediterranean catchment

Abstract: Future changes in climate may affect soil nitrogen (N) transformations, and consequently, plant nutrition and N losses from terrestrial to stream ecosystems. We investigated the response of soil N cycling to changes in soil moisture, soil temperature, and precipitation across three Mediterranean forest types (evergreen oak, beech, and riparian) by fusing a simple process-based model (which included climate modifiers for key soil N processes) with measurements of soil organic N content, mineralization, nitrific… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
15
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 60 publications
2
15
0
1
Order By: Relevance
“…Based on existing published data, we forecast that denitrification is not significant in riparian zones along low stream order streams under Mediterranean, arid or arctic climate due to low water availability and/or short residence time of water and solutes (Jones et al, 2005;Bernal et al, 2007;Mu et al, 2017;Poblador et al, 2017). Therefore, we forecast that in Mediterranean and arid regions, denitrification rates are consistently low compared to more humid catchments (Holmes et al, 1996;Bernal et al, 2007;Harms and Grimm, 2010;Lupon et al, 2015;Poblador et al, 2017). Yet, the capacity for denitrification can rapidly increase once waterlogged conditions develop in riparian zones (Harms et al, 2009).…”
Section: Riparian Corridors Function As Kidneys Of River Systemsmentioning
confidence: 80%
“…Based on existing published data, we forecast that denitrification is not significant in riparian zones along low stream order streams under Mediterranean, arid or arctic climate due to low water availability and/or short residence time of water and solutes (Jones et al, 2005;Bernal et al, 2007;Mu et al, 2017;Poblador et al, 2017). Therefore, we forecast that in Mediterranean and arid regions, denitrification rates are consistently low compared to more humid catchments (Holmes et al, 1996;Bernal et al, 2007;Harms and Grimm, 2010;Lupon et al, 2015;Poblador et al, 2017). Yet, the capacity for denitrification can rapidly increase once waterlogged conditions develop in riparian zones (Harms et al, 2009).…”
Section: Riparian Corridors Function As Kidneys Of River Systemsmentioning
confidence: 80%
“…No pulses of soil N cycling were detected in summer in the upland soils, which can be explained by their dryness (WFPS < 20%) (Lupon et al , ). Conversely, we recorded summer pulses of NNM and NN at the riparian site, probably because the riparian groundwater kept the soil relatively wet (WFPS > 30%) throughout the year, which was supported by the lack of correlation between ΣP4d and WFPS at this site.…”
Section: Discussionmentioning
confidence: 99%
“…Allison and Treseder (2008) reported that simultaneous temperature increase (0.5°C) and decline in water content (22%) of soil had negative effects on microbial respiration and bacterial and fungal abundances in boreal forest soils. The impacts of changed climate on soil nitrogen transformation processes (N-mineralisation, nitrification and denitrification) and nitrogen availability in various ecosystems (including forests) have been shown in many studies (Landesman and Dighton, 2010; Lupon et al, 2015). The characteristics of the climate change and concordant effect on N-cycling can be different according to the region (Lupon et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…The impacts of changed climate on soil nitrogen transformation processes (N-mineralisation, nitrification and denitrification) and nitrogen availability in various ecosystems (including forests) have been shown in many studies (Landesman and Dighton, 2010; Lupon et al, 2015). The characteristics of the climate change and concordant effect on N-cycling can be different according to the region (Lupon et al, 2015). Gerten et al (2008) showed that the magnitude of changes in carbon and water dynamics in response to changes in precipitation is determined by the degree of the ecosystem water limitation (ratio between atmospheric transitional demand and soil water supply) and seasonal timing of precipitation change (doubling or halving rather than altered frequency and intensity at constant annual amounts).…”
Section: Introductionmentioning
confidence: 99%